How a Realistic Magnetosphere Alters the Polarizations of Surface, Fast Magnetosonic, and Alfvén Waves. Issue 2 (7th February 2022) - Archer, M. O.; Southwood, D. J.; Hartinger, M. D.; Rastaetter, L.; Wright, A. N.
Abstract: System‐scale magnetohydrodynamic (MHD) waves within Earth's magnetosphere are often understood theoretically using box models. While these have been highly instructive in understanding many fundamental features of the various wave modes present, they neglect the complexities of geospace such as the inhomogeneities and curvilinear geometries present. Here, we show global MHD simulations of resonant waves impulsively excited by a solar wind pressure pulse. Although many aspects of the surface, fast magnetosonic (cavity/waveguide), and Alfvén modes present agree with the box and axially symmetric dipole models, we find some predictions for large‐scale waves are significantly altered in a realistic magnetosphere. The radial ordering of fast mode turning points and Alfvén resonant locations may be reversed even with monotonic wave speeds. Additional nodes along field lines that are not present in the displacement/velocity occur in both the perpendicular and compressional components of the magnetic field. Close to the magnetopause, the perpendicular oscillations of the magnetic field have the opposite handedness to the velocity. Finally, widely used detection techniques for standing waves, both across and along the field, can fail to identify their presence. We explain how all these features arise from the MHD equations when accounting for a non‐uniform background field and propose modified methods that might be applied to spacecraft observations. Plain Language Summary: Earth's magnetic environment in space, the magnetosphere, is a complex system within which ultra‐low frequency analogs to sound waves in the space plasmas present form various different types of resonance, somewhat like in musical instruments. Our understanding of such oscillations come from highly simplified mathematical models, which neglect many aspects of reality as they are difficult to include. By using computer simulations of the magnetosphere, however, we can compare the results from more representative conditions with our predictions from the easier theory. We find that while many features of the different waves present do indeed agree with expectations, some of the predictions become significantly altered by the use of a realistic magnetosphere. We explain how these differences arise and propose new techniques that take them into account, which might be used by those analyzing measurements of these waves from orbiting satellites. Key Points: A global MHD simulation shows system‐scale ULF waves' polarizations can significantly differ from box and dipole model predictions Phase or handedness reversals in the magnetic field compared to the velocity can occur simply due to the highly non‐uniform background field We propose modified detection techniques for spacecraft observations which account for the effects of a realistic magnetosphere